User Perspectives on Issues that Influence the Quality of Daily life of Ventilator-Assisted Individuals with Neuromuscular Disorders - Dina Brooks; Audrey King; Mark Tonack; Helen Simson; Maria Gould; Roger Goldstein (Canadian Respiratory Journal)
OBJECTIVES: To identify user perspectives on the issues that impact the quality of the daily lives of ventilator-assisted individuals living in the community.